2019
DOI: 10.1007/s40123-019-0189-3
|View full text |Cite
|
Sign up to set email alerts
|

Randomized Controlled Trial Comparing Everting Sutures with a Lateral Tarsal Strip for Involutional Lower Eyelid Entropion

Abstract: Introduction To compare the anatomical and functional outcome and changes in the quality of life (QoL) over time of the lateral tarsal strip (LTS) versus the Quickert everting sutures (ES) for the repair of primary involutional lower eyelid entropion. Methods Forty-five patients (54 eyes) with primary involutional lower eyelid entropion were recruited in a prospective randomized clinical trial over 3-year period. Twenty-six eyes were randomized to the LTS technique and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 36 publications
(36 reference statements)
0
15
0
2
Order By: Relevance
“…We read with great interest the recent article by Nakos et al that showed the lateral tarsal strip (LTS) to have superior surgical success rates and reduction of symptoms than Quickert everting sutures (ES) in the repair of primary involutional lower eyelid entropion after one year [1]. We wish to complement their findings with those of our own Yorkshire Entropion Study (not previously published)-a randomised controlled trial with long-term (12-year) follow-up in which we attempt to compare two techniques for the surgical correction of involutional entropion.…”
Section: Dear Sirmentioning
confidence: 99%
“…We read with great interest the recent article by Nakos et al that showed the lateral tarsal strip (LTS) to have superior surgical success rates and reduction of symptoms than Quickert everting sutures (ES) in the repair of primary involutional lower eyelid entropion after one year [1]. We wish to complement their findings with those of our own Yorkshire Entropion Study (not previously published)-a randomised controlled trial with long-term (12-year) follow-up in which we attempt to compare two techniques for the surgical correction of involutional entropion.…”
Section: Dear Sirmentioning
confidence: 99%
“…We thank Dr Jamison et al for their constructive comments on our recent publication [1]. The fact that this was only the second randomized controlled clinical trial (RCT) on involutional lower lid entropion indicates that there is a great need for scientific evidence in the field of oculoplastic surgery.…”
Section: Sirmentioning
confidence: 99%
“…Disagreements in the literature selection were resolved by discussion between the two investigators. Finally, two articles were selected [8,9] (Fig 1).…”
Section: Data Extractionmentioning
confidence: 99%
“…In the Nakos trial [8], one patient in the LTS group developed an abscess in the lateral canthal area at 12 months. In the Scheepers trial [9], a suture-related granuloma was observed with two patients in the ES group and no case of ectropion was observed.…”
Section: Fig 5 Forest Plots Of the Effect Sizes For Complications Atmentioning
confidence: 99%
See 1 more Smart Citation